Reconstituição paleoambiental e petrografia da formação pedra de fogo, permiano da bacia do Parnaíba, região de Filadélfia (Tocantins) - NETO ARAÚJO, Raphael (2019)
The Pedra de Fogo Formation from Parnaíba Basin, in Filadelfia region, Tocantins State, extends over an area of dozens of square kilometers and consists mainly of muddy facies. The faciological and stratigraphic analysis in outcrops allowed the recognition of 13 facies. These facies have been grouped into 7 facies associations (FA) that represent part of a lacustrine paleoenvironment associated with eolian dunes, inland sabkhas and, subordinately, ephemeral rivers. The lacustrine deposits (FA1) consist, predominantly, of mudstones with slightly undulating /planar lamination (Po facies) and, subordinately, of fine to medium sandstones with slightly undulating/planar lamination (Ao facies), forming centimetric to metric thickening-upward cycles. The lacustrine deposits with ephemeral rivers (FA2) consist of paraconglomerates and predominantly coarse and massive sandstones with scoured base structure (CAm facies), that are interpreted as a result of flash-flood episodes which caused channel flows to the marginal lacustrine zones. The lacustrine deposits with rests of fossilized wood (AF3) are composed of mudstones with slightly undulating/planar lamination (Po facies) with silicified fossils, classified preliminarily in the genera Psaronius. The inland sabkhas deposits (AF4) are characterized by the occurrence of medium sandstones with silicified evaporitic molds of popcorn and cauliflower kinds (facies Ame). Eolian dunes form restricted deposits and are represented by well sorted sandstones with small to medium-scale tangential (At facies) and trough (Aa2 facies) cross-bedding. The deposits of sheet flows (AF6) consist meanly of massive paraconglomerates (CAm facies) and are result of episodic sedimentation by flows not channeled. The facies association suspension lobes (AF7) is the only representative of Motuca Formation deposits and consists of fine to coarse sandstones with sigmoidal cross-bedding (As Facies) and the geometry of the strata forms sigmoid lobes suspended in the mudstones from Po facies.